Dr. An Introduction to Data Encryption and Future Trends in Lightweight Cryptography and Securing IoT Environments - Bagui, Sikha; Galliera, Raffaele (Transactions on Engineering and Computing Sciences, 2022)
This paper presents an overview of the basic concepts of cryptography and encryption. The work aims at presenting the main concepts and concerns of encryption on a high-level of abstraction, allowing non-domain expert readers to navigate through these topics. Less traditional arguments are also shown, from the relevance of Key Management Services with its usage in Envelope Encryption, to Zero Knowledge proofs and their innovative applications. The crucial importance of securing communications between IoT devices and widely used algorithms to do so, are also discussed.